The Factors Influencing Depression Endpoints Research (FINDER) study: final results of Italian patients with depression - Quail Deborah; Barraco Alessandra; Rossi Andrea; Caruso Rosangela; Grassi Luigi (Annals of General Psychiatry, 2010)
Abstract Background Factors Influencing Depression Endpoints Research (FINDER) is a 6-month, prospective, observational study carried out in 12 European countries aimed at investigating health-related quality of life (HRQoL) in outpatients receiving treatment for a first or new depressive episode. The Italian HRQoL data at 6 months is described in this report, and the factors associated with HRQoL changes were determined. Methods Data were collected at baseline, 3 and 6 months of treatment. HRQoL was measured using components of the 36-item Short Form Health Survey (SF-36; mental component summary (MCS), physical component summary (PCS)) and the European Quality of Life-5 Dimensions (EQ-5D; visual analogue scale (VAS) and health status index (HSI)). The Hospital Anxiety and Depression Scale (HADS) was adopted to evaluate depressive symptoms, while somatic and painful physical symptoms were assessed by using the 28-item Somatic Symptom Inventory (SSI-28) and a VAS. Results Of the initial 513 patients, 472 completed the 3-month observation and 466 the 6-month observation. The SF-36 and EQ-5D mean (± SD) scores showed HRQoL improvements at 3 months and a further smaller improvement at 6 months, with the most positive effects for SF-36 MCS (baseline 22.0 ± 9.2, 3 months 34.6 ± 10.0; 6 months 39.3 ± 9.5) and EQ-5D HSI (baseline 0.4 ± 0.3; 3 months 0.7 ± 0.3; 6 months 0.7 ± 0.2). Depression and anxiety symptoms (HADS-D mean at baseline 13.3 ± 4.2; HADS-A mean at baseline 12.2 ± 3.9) consistently decreased during the first 3 months (8.7 ± 4.3; 7.5 ± 3.6) and showed a further positive change at 6 months (6.9 ± 4.3; 5.8 ± 3.4). Somatic and painful symptoms (SSI and VAS) significantly decreased, with the most positive changes in the SSI-28 somatic item (mean at baseline 2.4 ± 0.7; mean change at 3 months: -0.5; 95% CI -0.6 to -0.5; mean change at 6 months: -0.7; 95% CI -0.8 to -0.7); in 'interference of overall pain with daily activities' (mean at baseline 45.2 ± 30.7; mean change at 3 months -17.4; 95% CI -20.0 to -14.8; mean change at 6 months -24.4; 95% CI -27.3 to -21.6) and in 'having pain while awake' (mean at baseline 41.1 ± 29.0; mean change at 3 months -13.7; 95% CI -15.9 to -11.5; mean change at 6 months -20.2; 95% CI -22.8 to -17.5) domains. The results from linear regression analyses showed that the antidepressant switch within classes was consistently associated with a worsening in SF-36 MCS, EQ-5D VAS and HSI compared to non-switching treatment. Furthermore, between-group antidepressants (AD) switch was associated with a worse SF-36 MCS and EQ-5D HSI. MCS (P = 0.028), PCS (P = 0.036) and HSI (P = 0.002) were inversely related to the number of each previous additional depressive episode. PCS (P = 0.009) and HSI (P = 0.005) were also less improved in patients suffering from a chronic medical condition. Moreover, PCS (P = 0.044) and EQ-5D VAS (P < 0.0001) worsening was consistently associated with the presence of a psychiatric illness in the 24 months before baseline. For every additional point on the SSI-somatic score and on the overall pain VAS score at baseline, HSI score were on average 0.062 (P < 0.001) and 0.001 (P = 0.005) smaller, respectively. Conclusions After starting AD treatment, HRQoL improvements at 3 and 6 months were observed. However, several factors can negatively influence HRQoL, such as the presence of somatic and painful symptoms, the presence of any chronic medical condition or previous psychiatric illness.